Effectiveness of Providing Local Food-Based Supplementary Food on Toddler Nutritional Status: A Review - Afifah Nur; Samsul (Journal of Health Science and Pharmacy, 2025)
Background: Malnutrition is a condition of nutrient deficiency or imbalance that affects growth, cognitive development, and overall health, and remains a significant health problem both globally and regionally. In the long term, high rates of stunting can threaten national welfare and resilience. The provision of Supplementary Feeding (Pemberian Makanan Tambahan or PMT) is an intervention aimed at addressing undernutrition in toddlers by providing safe, high-quality snacks that meet the nutritional needs of children, while also ensuring food safety and appropriate nutrient content. Objective: This study aims to analyze the effectiveness of supplementary feeding programs using local food ingredients in addressing nutritional problems in Indonesia. Method: This research is a systematic review conducted using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method. Articles included in the review focus on interventions involving supplementary feeding with local food to improve the nutritional status of toddlers. Results: The findings show that supplementary feeding programs based on local food ingredients are effective in improving the nutritional status of toddlers, particularly in reducing the prevalence of stunting and underweight. These programs support the principles of food diversity, balanced nutrition, and food safety. Several studies report improvements in anthropometric indicators such as weight-for-age and height-for-age after consistent provision of supplementary food sourced from local ingredients, such as fortified snacks, traditional food modifications, and nutrient-enriched complementary feeding. Conclusion: Supplementary feeding programs (PMT) utilizing local food ingredients are effective interventions for improving the nutritional status of toddlers in Indonesia. These programs not only address malnutrition but also promote food security and support local food resource utilization. Keywords: Nutritional status, stunting, supplementary feeding, local food, toddler nutrition